TINJAUAN ASPEK ERGONOMI DI RUANG PENYIMPANAN SUBBAGIAN REKAM MEDIS RSUD WALED KABUPATEN CIREBON - Widya Nurbaeti; Jaenudin; Iin Indra Nuraeni (Jurnal Kesehatan Mahardika, 2019)
In the storage section of the medical recordat the Waled public hospital. there are problems with ergonomics. high shelves cause medical record files difficult to reach and footing aids used in the form of a former wooden table drawer where the risk of falling to the officer at work, and the unavailability of room temperature indicators to measure ideal temperature and humidity as well as lack of lighting and less space stuffy. The purpose of this study was to review aspects of ergonomics in the medical record storage room. The Used of type research is descriptive. The used method is observation. The purpose of this study is to overview ergonomic aspects in the medical record storage room. The procedure for collecting data in this study is by observation and measurement. The used instrument is observation and measurement sheets. The population and samples in this study are medical record storage room and the officers. The used data analysis is univariate analysis. The research was conducted on 16 may 2019 at Waled public hospital of Cirebon district.From the results of the study about ergonomic aspects according to The International Ergonomic Association IEA, 2002 devided ergonomics into 4 categories. Physical ergonomics with percentage value of 80% and environmental ergonomics also with a percentage value of 80% do not meet ergonomics standard. Cognitive ergonomics with percentage value of 100% which has the same value with ergonomic Organization with percentage value of 100% meet ergonomics standard. it is suggested that hospital, especially in the filling room should replace foot pedestal devices, should use iron material ladders to advoid and reduce the risk of falling for officer. Should Install a temperature indicator or hygrometer in medical record storage room. Should Install curtains on glass windows, should clean the floor use a wet cloth to reduce dust and repair damage facilities and infrastructure in filling room.